2020
DOI: 10.3847/1538-4357/ab8015
|View full text |Cite
|
Sign up to set email alerts
|

A Hard X-Ray Test of HCN Enhancements As a Tracer of Embedded Black Hole Growth

Abstract: Enhanced emission from the dense gas tracer HCN (relative to HCO + ) has been proposed as a signature of active galactic nuclei (AGN). In a previous single-dish millimeter line survey we identified galaxies with HCN/HCO + (1-0) intensity ratios consistent with those of many AGN but whose midinfrared spectral diagnostics are consistent with little to no ( 15%) contribution of an AGN to the bolometric luminosity. To search for putative heavily obscured AGN, we present and analyze NuSTAR hard X-ray (3-79 keV) obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 75 publications
5
45
0
1
Order By: Relevance
“…This was done including, besides the 23 sources presented here, the 30 objects reported in Ricci et al (2017b), and several sources reported in recent literature (e.g. Iwasawa et al 2020;Privon et al 2020;Yamada et al 2020). Using X-ray spectroscopy, we identify a total of 35 AGNs in these systems, 5 of which are associated with U/LIRGs in the N stage (i.e.…”
Section: X-ray Agnmentioning
confidence: 99%
“…This was done including, besides the 23 sources presented here, the 30 objects reported in Ricci et al (2017b), and several sources reported in recent literature (e.g. Iwasawa et al 2020;Privon et al 2020;Yamada et al 2020). Using X-ray spectroscopy, we identify a total of 35 AGNs in these systems, 5 of which are associated with U/LIRGs in the N stage (i.e.…”
Section: X-ray Agnmentioning
confidence: 99%
“…Table 2 Correlation Coefficients between the Photoelectric Efficiency, as Defined by the Ratio of IR Cooling Lines to Mid-IR PAH Emission between 6 and 17 μm, and Other Quantities in GOALS Star-forming Galaxies Notes. Kendall's τ correlation coefficients (τ k ) and p-values were calculated using pymccorrelation (Privon et al 2020), which implements bootstrap error estimation on τ k and p with censored data (upper limits) as described in Curran (2014) and Isobe et al (1986) respectively. We report 16%, 50%, and 84% percentiles for each quantity.…”
Section: Dust Grain Properties and The Photoelectric Efficiencymentioning
confidence: 99%
“…In this case we turn to the method of Isobe et al (1986) for computing the Kendall tau correlation coefficient with censored data in both axes. We use the implementation of pymccorrelation (Privon et al 2020), which in turn perturbs the data in Monte Carlo fash- ion to compute the errors in the correlation coefficient (Curran 2014).…”
Section: Regressionsmentioning
confidence: 99%
“…Software: COSQUEST (Rupke 2021a), IFSFIT (Rupke 2014;Rupke & Veilleux 2015; Rupke 2021b), LINMIX_ERR (Kelly 2007), pymccorrelation (Privon et al 2020), scipy (Virtanen et al 2020), DRTOOLS (Rupke 2021c)…”
Section: Acknowledgmentsunclassified